What impact does trauma have on the at‐risk mental state? A systematic literature review. Issue 2 (30th May 2017) - Brew, Benjamin; Doris, Michael; Shannon, Ciaran; Mulholland, Ciaran
Abstract : Identification of individuals with an at‐risk mental state (ARMS) who are at a heightened risk of developing psychosis allows researchers and clinicians to identify what factors are associated with poorer outcomes and transitions to psychosis. A number of socioenvironmental factors are linked to an increase risk of developing psychosis, of which childhood trauma is widely acknowledged. The current review aims to examine what impact trauma has on the ARMS by reviewing reported relationships between trauma variables and transition to psychosis, ARMS severity, adaptive functioning and comorbid symptomology from both cross sectional and prospective design studies. A literature search was conducted for all relevant original research articles published in the English language up to December 2015 using 3 electronic databases: PsycINFO, Web of Science and PubMed. A total of 6 papers met the inclusion criteria and were included in the current review. Trauma was found to have a significant impact on the ARMS observed through reported relationships between trauma variables and transition to psychosis, ARMS severity, adaptive functioning and comorbid symptomology. Sexual trauma demonstrated the most consistent trauma variable to impact the ARMS. Individuals with an ARMS who have experienced sexual trauma are at a heightened risk of poorer outcomes and transitions to psychosis. Further prospective design studies are required to examine this observation further.